New catalysts for the conversion of methane to synthesis gas: Molybdenum and tungsten carbide - Claridge, J; York, A; Brungs, A; Marquez-Alvarez, C; Sloan, J; Tsang, S; Green, M (1998)
High-surface-area molybdenum and tungsten carbide materials, synthesised by the temperature programming reduction of the relevant metal oxide with methane/hydrogen, are highly efficient catalysts for the conversion of methane to synthesis gas, via the steam reforming, dry reforming, or partial oxidation processes. The activities of the carbides were found to be comparable to those of elemental iridium and ruthenium (well known to be active noble metal catalysts for the reforming of methane), and the conversion and product distribution were in accord with those calculated from the thermodynamic equilibria. At ambient pressure the carbides deactivated, in all the processes, due to the oxidation of the catalyst to MO2, while operation at elevated pressure (8 bar) resulted in stabilisation of the carbide and no catalyst deactivation for the duration of the experiments (72 h). HRTEM analysis showed that no macroscopic carbon was deposited on the catalysts during the catalytic reactions. The deactivation rate of the carbides reflected the strength of the oxidant used: oxygen > water ≅ carbon dioxide. A deactivation mechanism, via the insertion of O* resulting in oxide terraces is discussed, and two possible mechanisms for the production of synthesis gas by the methane dry reforming reaction over metal carbides are proposed: noble metal type and redox type. © 1998 Academic Press.